Активация пролиферации В-лимфоцитов мыши и циклические нуклеотиды в ранние стадии активации - Комиссаренко, С.В. (Биополимеры и клетка, 1988)
Показано, что активация В-лимфоцитов мыши сопровождается ранним Са-зависимым повышением cGMP, но не сАМР, в клетках, которого недостаточно для пролиферации лимфоцитов, останавливающихся в G₁- фазе клеточного цикла. Показано, що активація В-лімфоцитів миші супроводжується раннім Са-залежним підвищенням cGMP, але не сАМР, у клітинах, якого недостатньо для проліферації лімфоцитів, що зупиняються в G₁-фазі клітинного циклу. Splenocytes and isolated mouse spleen B lymphocytes were activated in culture by: antibodies to μ-chains of mouse immunoglobulins, Fab and F(ab')2 fragments of such antibodies, LPS from E. coli and interleukin 2(IL-2). Cell activation was monitored by [³H]-incorporation and by flow cytofluorimetry. The latter permitted detecting cell-cycle phases distribution of cells stained by acridine orange. It was shown that anti-μ antibodies were cytotoxic to mouse splenocytes and B lymphocytes. Isolated B cell could not be stimulated by Fab or F(ab')₂ anti-μ, fragments but were activated by LPS and by F(ab')₂ + IL-2, though F(ab')₂ were stimulative to mouse splenocytes. In most cases activated cells passed G₁ phase and were arrested at the GrS boundary. LPS or F(ab')₂ anti-μ, addition to isolated B cells in culture caused a Ca²⁺-dependent increase in cGMP but not cAMP levels in these cells. Methylene bisphosphonic acid being administered to mice 24 hours before B cells isolation did not change cAMP or cGMP levels in LPS of F(ab')₂ activated B lymphocytes. These data show that during the first minutes of B cell activation by LPS or F(ab')₂ anti-μ, fragments there occurs a Ca²⁺-dependent increase in the cGMP level which is not sufficient for these cells proliferation and progression through the whole cell-cycle. The cells are usually arrested in G₁ phase.